Association of peripheral blood pressure with gray matter volume in 19- to 40-year-old adults. (19th February 2019) - Schaare, H. Lina; Kharabian Masouleh, Shahrzad; Beyer, Frauke; Kumral, Deniz; Uhlig, Marie; Reinelt, Janis D.; Reiter, Andrea M.F.; Lampe, Leonie; Babayan, Anahit; Erbey, Miray; Roebbig, Josefin; Schroeter, Matthias L.; et al.
Abstract : Objective: To test whether elevated blood pressure (BP) relates to gray matter (GM) volume (GMV) changes in young adults who had not previously been diagnosed with hypertension (systolic BP [SBP]/diastolic BP [DBP] ≥140/90 mm Hg). Methods: We associated BP with GMV from structural 3T T1-weighted MRI of 423 healthy adults between 19 and 40 years of age (mean age 27.7 ± 5.3 years, 177 women, SBP/DBP 123.2/73.4 ± 12.2/8.5 mm Hg). Data originated from 4 previously unpublished cross-sectional studies conducted in Leipzig, Germany. We performed voxel-based morphometry on each study separately and combined results in image-based meta-analyses (IBMA) to assess cumulative effects across studies. Resting BP was assigned to 1 of 4 categories: (1) SBP <120 and DBP <80 mm Hg, (2) SBP 120–129 or DBP 80–84 mm Hg, (3) SBP 130–139 or DBP 85–89 mm Hg, (4) SBP ≥140 or DBP ≥90 mm Hg. Results: IBMA yielded the following results: (1) lower regional GMV was correlated with higher peripheral BP; (2) lower GMV was found with higher BP when comparing individuals in subhypertensive categories 3 and 2, respectively, to those in category 1; (3) lower BP-related GMV was found in regions including hippocampus, amygdala, thalamus, frontal, and parietal structures (e.g., precuneus). Conclusion: BP ≥120/80 mm Hg was associated with lower GMV in regions that have previously been related to GM decline in older individuals with manifest hypertension. Our study shows that BP-associated GM alterations emerge continuously across the range of BP and earlier in adulthood than previously assumed. This suggests that treating hypertension or maintaining lower BP in early adulthood might be essential for preventing the pathophysiologic cascade of asymptomatic cerebrovascular disease to symptomatic end-organ damage, such as stroke or dementia.